THE IMAGE OF WOMEN IN THE POEMS "PEREMPUAN PERKASA" BY SUSILANING SETYOWATI HARDJONO AND "PEREMPUAN-PEREMPUAN PERKASA" BY HARTOJO ANDANGDJAYA (COMPARATIVE LITERARY STUDIES) - Fatimah, Siti Nur; Destriana, Arivianti; Wulandari, Yosi (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2024)
Abstract The problem of women's stereotypes is often exploited by authors in building story structures. The image of women in comparative literary studies in the poem entitled "Perempuan Perkasa" by Susilaning Setyowati Hardjono and "Perempuan-Perempuan Perkasa" by Hartojo Andangdjaja depicts the stereotype of women in society. The purpose of this research is to find out the comparison of the two poems in terms of the image of women. The research method used is descriptive qualitative. The research results obtained are the image of women. The image of women in the poem entitled "Perempuan Perkasa" by Susilaning Setyowati Hardjono found physical aspects, namely women when pregnant, giving birth and giving breast milk; soul image: patience in facing life; psychic image found strong thoughts fighting for freedom of rights; Social image found that women are able to socialize in society without making distinctions. Meanwhile, in the poem "Perempuan-Perempuan Perkasa" by Hartojo Andangdjaja, aspects of the physical image of being able to support hard work are found; the image of a soul full of love for family; a psychic image that is able to use its thinking to earn a living; social image of looking for a living in city markets to meet people's needs.